Sistem Informasi Pemesanan Jasa Wedding Organizer pada Youzhie Penganten dengan Menggunakan Bahasa Pemograman PHP Dan MySQL - Vicky Ariandi (Majalah Ilmiah UPI YPTK, 2019)
Web design Ordering Wedding Organizer Services at Youzhie Bride aims to make it easier for the public to obtain information on ordering wedding services (online) that were previously known from the mouth of the mouth so that they can save time, here I make it easier for people to order online so they can be efficient and effective . This final project can help in building an online ordering system. The design system in making websites Ordering Wedding Organizer Services at Youzhie The bride was developed using several software namely xampp, Notepad ++, Server which is a combination of Web Server, PHP and MySQL